Assessing climate adaptation options for cereal-based systems in the eastern Indo-Gangetic Plains, South Asia - Tesfaye, Kindie; Erenstein, Olaf; Khatri-Chhetri, Arun; Aggarwal, Pramod K.; Mequanint, Fasil; Shirsath, Paresh Bhaskar; Stirling, Clare M; Jat, Mangi Lal; Rahut, Dil Bahadur (Cambridge University Press, 2019)
New farming systems and management options are needed in South Asia as the intensive rice–wheat production system is set to become increasingly unsustainable under climate change. In the current study, six cropping systems options/treatments varying in tillage, crop establishment method, residue management, crop sequence and fertilizer and water management were evaluated using a cropping systems model under current (1980–2009) and future (2030 and 2050) climate scenarios in the state of Bihar, India. The treatments were current farmers’ practice (CP), best fertilizer and water management practices, zero tillage (ZT) with no crop residue retention, ZT with partial crop residue retention (ZTPR), future conservation agriculture-based rice–wheat intensive cropping system (FCS-1) and future conservation agriculture-based maize–wheat intensive cropping system (FCS-2). The results indicate that climate change is likely to reduce rice–wheat system productivity under CP by 4% across Bihar. All the crop management options studied increased yield, water productivity and net returns over that of the CP under the current and future climate scenarios. However, the ZTPR treatment gave significantly higher relative yield, lower annual yield variability and a higher benefit-cost-ratio than the other treatments across cropping system components and climate periods. Although all the new cropping system treatments had a positive yield implication under the current climate (compared to CP), they did not contribute to adaptation under the future climate except FCS-2 in wheat. It is concluded that adaptation to future climate must integrate both cropping system innovations, and genetic improvements in stress tolerance.